The relationship between religious coping with body image concern among patients on hemodialysis: the mediating role of self-care - Sharif-Nia, Hamid; Marôco, João; Sivarajan Froelicher, Erika; Jaafari, Badri; Moshtagh, Mozhgan; Khoshnavay Fomani, Fatemeh; Goudarzian, Amir Hossein; Kaveh, Omolhoda (Frontiers in Psychology, 2025)
ObjectiveExploring the factors that contribute to body image concerns among patients on hemodialysis is imperative. This cross-sectional study investigates whether self-care mediates the relationship between religious coping and body image concerns.MethodsA total of 398 patients completed the Littleton’s Body Image Concern Inventory Questionnaire, Assessment of Self-care Behaviors with Arteriovenous Fistula, and Religious Coping Questionnaire between February and May 2023 at a major comprehensive hemodialysis center in Iran.ResultsThe mean age of patients on hemodialysis was 56.97 (SD = 13.48). The model explained 23.5% of the variation observed in body image concern (R2 = 0.235, p < 0.001). However, the mediation effect of self-care on body image was not statistically significant (β = 0.13, p = 0.434). In contrast, a mid-sized significant direct effect of religious coping on body image concerns was observed (β = 0.13, p < 0.001).ConclusionThe study contributes to the existing literature on the relationship between religious coping, body image concern, and self-care in various populations, such as overweight and obese individuals, high school students, and young females. The findings highlight that religious coping has directl relationship with body image concerns among patients on hemodialysis, while the mediating role of self-care was not supported. These results underscore the need for further research and targeted interventions that consider spiritual coping to improve body image outcomes in this population.